KEDONDONG, DURIAN, DAN MANGGIS SEBAGAI IDE UNGKAPAN DALAM SENI LUKIS SUREALIS - Asep Kurniawan, Drs. Erfahmi, M.Sn., Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2016)
The purpose of this final project is to explore the problem of hypocritical, honesty, and persistence through metamorphosis of Kedondong, Durian, and Mangosteen fruits into artwork of Surealist. The manifestation of art idea and supportive element as a subject matter which has sense and philosophy in that object. In its creating process, writer is using oil, and acrylic paint on the canvas by using Realist technique. The style that is used here is Surealist, a style that shows a freedom of creativity beyond the imagination, one of the characteristic is the change on the object. All 10 of the writer works have meaning about hypocritical, honesty and persistence in political environment and all of the works meaning appear in both positive and negative way.Key-Term : Kedondong, Durian, Mangosteen, Fine Art, Surealist